ECC Based Load Information Protection Scheme for Electric Vehicle Users - Renwu YAN; Yang ZHENG; Zhixiong LIN; Yihan LIN; Zhipeng YU; Wenfeng ZHANG (Zhongguo dianli)
In the trend of smart grid, data transmission and exchange between power companies and users become more frequent and efficient. The communication network is often attacked or eavesdropped. In order to ensure that the user 's electricity data is not maliciously tampered during transmission, an information protection scheme for electric vehicle users is proposed. By improving the addition operation and scalar multiplication operation, the traditional elliptic curve cryptography（ECC） is lightly optimized to overcome the problem of limited smart meter resources in the two-way interactive environment of the power grid. On this basis, the load decomposition algorithm is designed as a test tool for the encryption scheme to decompose the encrypted power data. Finally, the reliability and security of the proposed scheme are verified by a simulation example.